Quiescent Optical Solitons for the Concatenation Model Having Nonlinear Chromatic Dispersion and Kerr Law of Self-Phase Modulation (Contemporary Mathematics, 2025)
This paper focuses on the retrieval of quiescent optical solitons within the framework of the concatenation model, incorporating nonlinear chromatic dispersion and the Kerr law of self-phase modulation. These solitons, which remain stable and maintain their shape over time, are crucial for understanding the behavior of light in nonlinear optical media. The retrieval of these solitons is achieved through two distinct techniques. Each of these integration schemes offers a systematic way to derive analytical solutions, ensuring that the underlying dynamics of the optical solitons are accurately captured. In addition to the analytical solutions, this study presents numerical simulations to validate the theoretical findings. These simulations illustrate the behavior of the recovered quiescent solitons, confirming their stability and showcasing their dynamics under the influence of self-phase modulation and nonlinear chromatic dispersion. By bridging analytical methods with computational validation, the paper offers a thorough examination of these soliton structures and their real-world relevance, particularly in the design of advanced optical fiber networks and nonlinear optical devices.
Keywords: methods, model, solitons, Riccati, dispersion